Extraction of glucose from kenaf core using mild acid treatment - Seeni Mohamed, Nurhafizah; Mel, Maizirwan; Anuar, Hazleen; Othman, Rashidi; Mohd Nasir, Nur Aimi (2012)
Recently, many industries are aims to reduce the usage of petroleum based product or synthetic fibre due to the increment of the environmental consciousness. This has lead to the extensive research on the natural fibre in order to produce eco–friendly product that will replace the existing petroleum based products. Natural fibre can be derived from many sources such as plants, animals or minerals. However the plant fibre such as kenaf is more desirable by most of the researcher. Kenaf or scientifically known as Hibiscus cannabinus. L has a complex structure because it consists of lignin, cellulose and hemicelluloses. Due to this reason, kenaf need to undergo treatment process in order to remove lignin and hemicellulose, reduce crystallinity of cellulose and increase porosity. In this study, acid treatment method was used with several parameters process such as temperature and time for getting high yield of glucose conversion. The substantially highest glucose yield was 3.4 g/L produced at 200 ºC for 60 minutes.